2012
DOI: 10.1108/02637471211198161
|View full text |Cite
|
Sign up to set email alerts
|

Home sustainability policy and mandatory disclosure

Abstract: Purpose -Sustainability Declarations were introduced by the Queensland State Government on 1 January 2010 as a mandatory disclosure measure for all dwelling sales in the State. The purpose of this paper is to assess the impact this policy decision has had in the homebuyer decision-making process in the first year since its introduction and to consider the effectiveness of the legislation in meeting its policy objectives. Design/methodology/approach -This quantitative research comprised a two-part process: the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The attitude of agents not actively promoting sustainability features may affect potential sellers/buyers not realising the importance of choosing a home with sustainability features [70]. In this context, policy measures such as the mandatory disclosures of sustainability policy by the Queensland State Government in Australia are positive steps towards promoting a smart and sustainable real estate sector that can increase homebuyers awareness about sustainability and help them make better and informed decisions [71]. Further, in the current times of restrictions on physical inspections and social distancing, most of the control and information disclosure powers are in the hands of the agents, who can manipulate the data fed to consumers.…”
Section: Agents (Ag)mentioning
confidence: 99%
“…The attitude of agents not actively promoting sustainability features may affect potential sellers/buyers not realising the importance of choosing a home with sustainability features [70]. In this context, policy measures such as the mandatory disclosures of sustainability policy by the Queensland State Government in Australia are positive steps towards promoting a smart and sustainable real estate sector that can increase homebuyers awareness about sustainability and help them make better and informed decisions [71]. Further, in the current times of restrictions on physical inspections and social distancing, most of the control and information disclosure powers are in the hands of the agents, who can manipulate the data fed to consumers.…”
Section: Agents (Ag)mentioning
confidence: 99%
“…Furthermore, Moore & Hurst [30], after interviewing households in Melbourne, concluded that attributes such as location, affordability, and the number of bedrooms/bathrooms were the main considerations in house selection, while sustainability was seldom indicated. In Queensland, Bryant & Eves [31] using surveys applied to realtors, assessed whether sustainability features were important in the house purchase decision; they found that 96% of buyers do not consider such attributes important in their decision-making process. The same conclusions were drawn in the study of Eves & Kippes [32] based on surveys to home buyers in New Zealand; aspects such as location and price were the buyers' main concerns, although energy-efficiency and green housing issues appeared as major concerns for the tier of younger and older buyers in the high-income brackets.…”
Section: Brief Literature Review and Issues Around The Epbd Spanish Imentioning
confidence: 99%